Does warehouse receipt financing benefit Ghanaian smallholders? - Miranda, Mario; Mulangu, Francis; Kemeze, Francis H.; Kolavalli, Shashidhara (International Food Policy Research Institute, 2018)
In practice, however, warehouse receipt financing has generally failed to deliver the benefits to smallholders hoped for by development economists and practitioners. In Ghana, and more generally throughout Africa, warehouse receipt financing is currently used almost exclusively by large traders, processors, and exporters. In this brief, we explore reasons why smallholders have shunned warehouse receipt financing and discuss policy prescriptions that could make warehouse receipt financing more accessible and beneficial to them.